Surface-Enhanced Raman Scattering of MEH-PPV on Gold and Silver Nanoparticles - Beatriz R. Moraes; Nathalia S. Campos; Alvaro C. C. Barra; Celly M. S. Izumi (Journal of Spectroscopy)
The interaction of poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylenevinylene] (MEH-PPV) with Au or Ag nanospheres, Au nanostars, and Ag nanoprisms was investigated using surface-enhanced Raman scattering (SERS). The SERS investigation showed that adsorption of MEH-PPV strongly depends on the nature of the nanoparticle surface. On gold nanostars that present a thick layer of capping polymer, SERS spectrum is only observed in relatively concentrated MEH-PPV solution (1 mmol L−1). On the other hand, Au and Ag nanospheres present SERS spectra down to 10−6 mol L−1 and no chemical interaction of MEH-PPV and metal surface is observed. The spectra of MEH-PPV on Ag nanoprisms with PVP as stabilizing agent suggest that the capping polymer induces a planar conformation of MEH-PPV and consequently an increase of conjugation length. These results give support for the application of MEH-PPV on optoelectronics in which interfacial effects are critical in the device efficiency and stability.